Assessing the Impact of Unresolved Waste Management on Human Capital Development in Indonesia: An Empirical Analysis - Alice Erni Husein (Eduvest - Journal of Universal Studies, 2026)
Indonesia is confronting a severe waste management crisis that increasingly threatens not only environmental sustainability but also human capital development. Rapid population growth and inadequate waste infrastructure have resulted in widespread open dumping and burning, while government spending and strategic planning remain limited. This study seeks to shed light on the future implications for Indonesian human capital based on data gathered from recent empirical studies. Using a Systematic Literature Review combined with bibliometric analysis through the Biblioshiny tool in R, the study compares the impacts in urban and rural settings. It examines how ineffective waste management degrades environmental quality, harms public health, and undermines the nation’s human capital, with broader implications for economic development. The findings highlight the urgent need to integrate waste management into national development strategies, emphasizing that improving collection systems, recycling initiatives, and sanitary disposal practices can enhance public health, promote green employment opportunities, and strengthen the human capital essential for sustainable economic development.